Pengaruh Pemberian Bolu Pisang Ambon Terhadap Perubahan Tekanan Darah Penderita Hipertensi Di Wilayah Kerja Puskesmas Soropia Kabupaten Konawe - Sabina, Riska Adni; Ananda, Siti Hadrayanti; Demmalewa, Jenni Qlifianty; Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Hypertension is when the pressure in blood vessels increases above 120/80 mmHg. Blood pressure goal is less than 130/80 mmHg, and when the pressure is 140/90 mmHg or higher, it called as hypertension. One of non-pharmacology therapies used to lower high blood pressure is giving ambon banana cake to the patients with hypertension at Soropia health centre, Soropia district, Konawe. This is a quantitative study used quasi-experiment of pre test and post test with control group design. The observation was conducted twice-before and after treatment. Population of the study were 19 people who suffered hypertension at Soropia health centre, Soropia district, Konawe. 16 people were chosen by using Slovin formula to obtain representative samples. Then, 16 people were divided into 2 groups (8 People were in control group and others were in intervention group). Result of Wilcoxon test concluded that there’s an effect of non-pharmacology therapy by giving Ambon banana cake on blood pressure changes of patients with hypertension